Biomimetic Nanocones that Enable High Ion Permselectivity. (2nd August 2019) - Shehzad, Muhammad A.; Wang, Yaoming; Yasmin, Aqsa; Ge, Xiaolin; He, Yubin; Liang, Xian; Zhu, Yuan; Hu, Min; Xiao, Xinle; Ge, Liang; Jiang, Chenxiao; Yang, Zhengjin; et al.
Abstract: Artificial counterparts of conical‐shaped transmembrane protein channels are of interest in biomedical sciences for biomolecule detection and selective ion permeation based on ionic size and/or charge differences. However, industrial‐scale applications such as seawater desalination, separation of mono‐ from divalent cations, and treatment of highly‐saline industrial waste effluents are still big challenges for such biomimetic channels. A simple monomer seeding experimental approach is used to grow ionically conductive biomimetic charged nanocone pores at the surface of an acid‐functionalized membrane. These readily scalable nanocone membranes enable ultra‐fast cation permeation (Na + =8.4× vs. Mg 2+ =1.4×) and high ion charge selectivity (Na + /Mg 2+ =6×) compared to the commercial state‐of‐the‐art permselective membrane (CSO, Selemion, Japan) owing to negligible surface resistance and positively charged conical pore walls. Abstract : Nanokegel‐Öffnungen mit vernachlässigbarem Oberflächenwiderstand erlauben den Eintritt aller Kationen in eine Membran und ermöglichen ultraschnelle Kationenpermeation. Ein starker Abfall in Kegeldurchmesser und positiver Ladung an der Kegelwand sowie darunterliegenden Nanoporen führt zu starker sterischer Hinderung und elektrostatischer Abstoßung gegenüber Mg 2+ im Vergleich zu kleineren Na + ‐Ionen, was eine hohe Na + /Mg 2+ ‐Selektivität ermöglicht.